Research on Network Marketing of Ancient Style Dolls in Ancient Western Regions Based on Interactive Experience - Yang, Dan; Areerungruang, Supachai (Journal of Multidisciplinary in Humanities and Social Sciences, 2024)
With the rapid development of information technology, the figure art in ancient western areas has occupied the mainstream position in the art market with its characteristics of openness, freedom and interdimensionality, among which Xinjiang figure art is the most typical. This paper aims to study: 1) Take Xinjiang Doll as the representative, discuss the integration of mobile Internet technology and traditional art market, the development and transformation process of online doll art platform, and investigate the formal characteristics of online art trading on the basis of interactive experience. (2) Combined with the subject knowledge of interactive experience, through the questionnaire survey and interview of target consumers, the current digital interactive technology is used to analyze the shortcomings of the marketing mode of art e-commerce platform from the perspective of interactive experience, and then put forward targeted optimization strategies and try to formulate feasible plans. This paper uses a questionnaire to interview consumers who choose Xinjiang Doll, and collects feedback data on the online platform, and analyzes the data through descriptive statistics and content analysis. The findings are as follows: (1) With the development of various art e-commerce, the collection of Xinjiang dolls has become popular, and art information has become transparent. Online art fairs will replace most offline marketing models. (2) the continuous optimization of interactive experience has led the development of the entire Internet industry. (3) New online platforms need to be based on the concept of people-oriented, and should constantly update the interaction method and optimize the interactive experience.